Increased diagnostic yield in complex dystonia through exome sequencing. (May 2020) - Wirth, Thomas; Tranchant, Christine; Drouot, Nathalie; Keren, Boris; Mignot, Cyril; Cif, Laura; Lefaucheur, Romain; Lion-François, Laurence; Méneret, Aurélie; Gras, Domitille; Roze, Emmanuel; Laroche, Cécile; et al.
Abstract: Introduction: A strategy based on targeted gene panel sequencing identifies possibly pathogenic variants in fewer than 20% of cases in early-onset and familial form of dystonia. By using Whole Exome Sequencing (WES), we aimed to identify the missing genetic causes in dystonic patients without diagnosis despite gene panel sequencing. Material and methods: WES was applied to DNA samples from 32 patients with early-onset or familial dystonia investigated by sequencing of a 127 movement disorders-associated gene panel. Dystonia was described according to the familial history, body distribution, evolution pattern, age of onset, associated symptoms and associated movement disorders. Rate of diagnoses was evaluated for each clinical feature. Results: We identified causative variants for 11 patients from 9 families in CTNNB1, SUCLG1, NUS1, CNTNAP1, KCNB1, RELN, GNAO1, HIBCH, ADCK3 genes, yielding an overall diagnostic rate of 34.4%. Diagnostic yield was higher in complex dystonia compared to non-complex dystonia (66.7%–5.9%; p < 0.002), especially in patients showing intellectual disability compared to the patients without intellectual disability (87.5%–16.7%; p < 0.002). Conclusion: Our approach suggests WES as an efficient tool to improve the diagnostic yield after gene panel sequencing in dystonia. Larger study are warranted to confirm a potential genetic overlap between neurodevelopmental diseases and dystonia. Highlights: We aimed to identify the missing genetic causes in dystonia after targeted sequencing. By using exome sequencing, we obtained a diagnostic yield of 34.4%. The rate of diagnoses was higher in complex dystonia. WES appears to be an efficient tool to improve the diagnostic yield in dystonia.